Does The Existence of Sharia Microfinance Institutions Contribute to Agricultural Financing? (Study at BMT Khairul Amin Martapura) - Ermawati Ermawati; Zaki Mubarak (Universitas Islam Lamongan, 2023)
Baitul Mal wa Tamwil (BMT) is a Microfinance institution that boosts the economy in the MSME sector. BMT is expected to reach the agricultural sector. In some cases, capital is still weak in the agricultural sector. The establishment of the BMT Khairul Amin Martapura Rangas River branch is expected to help the community, especially farmers, solve the capital problems. This research is field research using qualitative method approach. In addition to producing qualitative data results, this research uses a simple quantitative approach to strengthen the analysis results by explaining the data with numbers. There are six informants in the study. The results revealed that the existence and accessibility of BMT are pretty good. However, in the agricultural sector, it is still not good because the percentage of farmer customers is only 21.05%, and the financing disbursed is only 35.04%.